ATG13 is involved in immune response of pathogen invasion in blood clam Tegillarca granosa - Yuling Wu; Yuling Wu; Guosheng Liu; Zengpeng Li; Mingliang Chen; Mingliang Chen; Mingliang Chen; Qin Wang (Frontiers in Veterinary Science, 2023)
Mammalian autophagy-related gene 13 (ATG13) is a vital component of the ATG1 autophagy initiation complex which plays an essential role in autophagy. However, the molecular function of ATG13 in pathogen defense in invertebrates is still poorly understood. In this study, the full-length cDNA sequence of blood clam Tegillarca granosa ATG13 (TgATG13) was obtained, which was 1,918 bp in length, including 283 bp 5' UTR, 252 bp 3' UTR and 1,383 bp open reading frame (ORF) encoding 460 amino acids. Phylogenetic analysis revealed that TgATG13 had the closest relationship with that of Crassostrea Virginica. Quantitative real-time PCR results showed that the transcript of TgATG13 was universally expressed in various tissues of blood clam, with the highest expression level in hemocytes. The expression level of TgATG13 was robustly increased after exposure of both Vibrio alginolyticus and LPS. Fluorescence confocal microscopy further showed that TgATG13 promoted the production of autophagosome. In summary, our study demonstrated that TgATG13 was involved in the immune regulation of blood clam during pathogen invasion, deepening our understanding of the innate immune mechanism of blood clam.